Man, the state, and war a theoretical analysis - Waltz, Kenneth N. (New York Columbia University Press, 2001)
What are the causes of war? To answer this question, Professor Waltz examines the ideas of major thinkers throughout the history of Western civilization. He explores works both by classic political philosophers, such as St. Augustine, Hobbes, Kant, and Rousseau, and by modern psychologists and anthropologists to discover ideas intended to explain war among states and related prescriptions for peace.
Includes bibliographical references (p. [239]-251) and index.
Keywords: International relations--Philosophy.